Towards a Formant-Based Model of Sundanese Vowel Distinction: Evidence of Gender-Dependent Acoustic Patterns in /è/, /e/, and /eu/ - Suwandi, Galih Restu Fardian; Julaeha, Juju; Khairina, Jasmine; Rohman, Syifa Nailufar (Fakultas Matematika dan Ilmu Pengetahuan Alam, Univetsitas Tanjungpura, 2025)
The fundamental frequency (pitch or F0) is the lowest in a sound signal, while the formant frequency is the resonant frequency that occurs in the vocal track. Both are acoustic parameters that are essential to identify sound signals. The pitch and formant are extracted from the subject, which consisted of 16-17-year-old Sundanese, 20 males and 20 females. Praat software extracts pitch and the first to fourth formant (F1-F4) on each sound signal of the letters /è/, /e/, and /eu/. The analysis showed that each vowel /è/, /e/, and /eu/ in males had a smaller pitch and formant than in females, with gradient differences /è/, /e/, and /eu/ was 48.22, 157.49, and 136.27. Regarding the significant level Two Tailed T-Test statistic calculation, most formant frequency comparisons of 2 vocals (/è/ and /e/, /e/ and /eu/, /è/ and /eu/) are significantly distinguished. The study also showed that several vocals had an undistinguished formant frequency at F3. It can be concluded that the pronunciation of /è/, /e/, and /eu/ between males and females can be identified through the fundamental and formant frequency.